Тайм-менеджмент для IT спеціалістів - Лейба, Я. А. (ХНУРЕ, 2020)
Have you ever faced with the situations where a company repeatedly postpones release date for their project, when you have been waiting for days, months or even years and the release day is changed constantly? Perhaps, most of you have come across this. There are a lot of reasons for this decision – technical issues, project polishing, bug fixes, staff change, financing, improperly planned schedule, implementation of new features, etc. The exact reason depends on the particular case. It is known that almost all IT specialists have 8-10-hours shifts. Sometimes, due to lack of time/resources, they have to take over shifts or to transfer their projects to another team/company (outsource) to complete the project in time. In this article, we will discuss the importance of time management.
Keywords: філософія; тайм-менеджмент